Segmental resection of the main left bronchus due to adenoid cystic carcinoma - Chrząstek, Aleksandra; Bławat, Przemysław; Żołna, Łukasz; Kowalewski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Adenoid cystic carcinoma (ACC) is a rare type of cancer characterized by low malignancy, average metastasis potential and a relatively good prognosis. It occurs most often within the head and neck area. Within the respiratory tract, it most commonly occurs in the trachea or main bronchi. It originates from the glands located under the mucous membrane. It occurs more often in females (60%), and has no confirmed connection to smoking [1]. Common symptoms of ACC located within the respiratory tract are: breathlessness, productive cough, with or without blood spitting, weakness and decrease in effort tolerance.